A social bot in support of crisis communication: 10-years of @LastQuake experience on Twitter - Bossu, Rémy; Corradini, Marina; Cheny, Jean-Marc; Fallou, Laure (Frontiers in Communication, 2023)
Social media such as Facebook or Twitter are at present considered part of the communication systems of many seismological institutes, including the European–Mediterranean Seismological Center (EMSC). Since 2012, the EMSC has been operating a hybrid Twitter system named @LastQuake comprising a bot for rapid information on global felt earthquakes and their effects, which is complemented by manual moderation that provides quasi-systematic and rapid answers to users' questions, especially after damaging earthquakes and earthquake sequences. The 2022 release of @LastQuake transcends a mere alert service and possessess additional capabilities, including fighting against misinformation and enhancing earthquake risk awareness and preparedness by exploiting the teachable moments opened by widely felt but non-damaging earthquakes. @LastQuake significantly increases the visibility and audience of the European–Mediterranean Seismological Center services, even in regions where its smartphone application (app) and websites are well known. It also contributes to increasing the volume of crowdsourced eyewitness observations that are collected, notably through the publication of rapid non-seismic-wave-based detections, as well as by reaching out to Twitter users who post about felt experiences through individual invitation messages. Although its impact, especially in raising awareness and preparedness is difficult to evaluate, @LastQuake efficiently supports crisis communication after large earthquakes and receives positive feedback from users for satisfying identified information needs of eyewitnesses automatically and in a timely manner. This study shares the experience gained over the last 10 years of operating the bot, presents the impact of users' feedback on empirically driving its evolution, and discusses the ways by which we can move toward a more data-driven assessment of its impact.